2004
DOI: 10.1080/02791072.2004.10399722
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Outcomes of Best-Practice and Research-Based Outpatient Treatment Protocols for Adolescents

Abstract: Comparisons of well-developed practice-based interventions with research-based interventions are rare. This quasi-experimental study compares the outcomes of 274 adolescents (75% male; 63% weekly+ users; 54% dependent; 27% prior treatment; 73% with co-occurring problems) who received Chestnut Health System's best-practice Outpatient Treatment (CHS) or Cannabis Youth Treatment (CYT) research-based interventions. Ninety-five percent of participants completed follow-up interviews at three, six, nine, and 12 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…We also found that adolescents with the most serious clinical issues or behavioral problems at intake (e.g., high levels of victimization, Conduct Disorder, or truancy) were more likely to still report using some substances at six month follow-up and some problem behaviors, as also reported by other studies that do not consider treatment engagement (Arria, 2003; Godley et al, 2004b; Luchansky et al, 2006a; Williams et al, 2008). By and large, however, we did not confirm other research showing that co-morbid mental health disorders negatively influence abstinence (Godley et al, 2004a; Hser et al, 2003a; Tomlinson et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…We also found that adolescents with the most serious clinical issues or behavioral problems at intake (e.g., high levels of victimization, Conduct Disorder, or truancy) were more likely to still report using some substances at six month follow-up and some problem behaviors, as also reported by other studies that do not consider treatment engagement (Arria, 2003; Godley et al, 2004b; Luchansky et al, 2006a; Williams et al, 2008). By and large, however, we did not confirm other research showing that co-morbid mental health disorders negatively influence abstinence (Godley et al, 2004a; Hser et al, 2003a; Tomlinson et al, 2004).…”
Section: Discussionsupporting
confidence: 84%
“…Our finding that studies in which substance use intervention was based partly or completely on the 12-step philosophy had high attendance rates is consistent with previous findings that integrating 12-step concepts in professional substance use treatments and referring to 12-step groups is related to higher 12-step attendance (Godley, Jones, Funk, Ives, & Passetti, 2004;Kaskutas, Subbaraman, Witbrodt, & Zemore, 2009;Timko & DeBenedetti, 2007;Tonigan, Connors, & Miller, 2003). Including the 12-step approach in the treatment may be a way to increase attendance rates within the adolescent population.…”
Section: Discussionsupporting
confidence: 92%
“…In a quasi-experiment (Godley et al, 2004), outcomes for 274 adolescents were compared with those who received either Chestnut Health System’s Bloomington Outpatient Treatment (CBOP; Godley et al, 2003) or one of three research-based interventions (including MET/CBT) in the CYT study (Dennis et al, 2004). Adolescents in the CBOP cohort had significantly longer lengths of stay and received over three times as many hours of treatment.…”
Section: Introductionmentioning
confidence: 99%